PENINGKATAN KETERAMPILAN MENYUSUN TEKS DESKRIPSI MELALUI PEMBELAJARAN DENGAN MEDIA MIND MAP PADA SISWA KELAS VII A SMP NEGERI 16 KOTA JAMBI TAHUN AJARAN2018/2019 - Rosniati Rosniati (Universitas Batanghari, 2021)
This classroom action research examines the improvement of the ability to write descriptive texts in class VII A students of SMP Negeri 16 Jambi City. The purpose of this study was to determine the increase in compiling descriptive text through learning using mind map media which is feasible for descriptive text material in Indonesia based on the 2013 curriculum in Keels VII A students of Negeri 16 Jambi City. The process of classroom action research is carried out in two cycles, each of which includes four main stages, namely planning, acting, observing and reflecting. The instruments used were test and non-test. Test instrument to get the score of the ability to write descriptive text. The non-test instrument used by the researcher was a journal, an observation guide to obtain data about the student's ability to write descriptive texts. The results show that using mind map media can improve the ability to write descriptive text for class VII A students of SMP Negeri 16 Jambi City for the 2018/2019 academic year. (1) The value of the learning process based on the aspects of compiling the descriptive text increased from cycle I to cycle II by 90, (2) In addition, based on the test the ability to write descriptive text increased from cycle I to cycle II. Then from the initial conditions to cycle one there was an increase of 30% or from 30% to 60%. In cycle I to cycle II it is 25% or from 60% to 85%. The results of the above analysis show that the action hypothesis in this study is in line with the expectation that the use of mind map media can improve the ability to write descriptive texts. The results of this research can provide benefits for schools, field teachers and students, especially those related to improving the ability to write descriptive texts.